African Herbal Medicines: Adverse Effects and Cytotoxic Potentials with Different Therapeutic Applications - Okaiyeto, Kunle (Int J Environ Res Public Health, 2021)
The African continent is naturally endowed with various plant species with nutritional and medicinal benefits. About 80% of the people in developing countries rely on folk medicines to treat different diseases because of indigenous knowledge, availability, and cost-effectiveness. Extensive research studies have been conducted on the medicinal uses of African plants, however, the therapeutic potentials of some of these plants has remained unexploited. Over the years, several studies have revealed that some of these African floras are promising candidates for the development of novel drugs. Despite the plethora of studies on medicinal plant research in Africa, there is still little scientific data supporting the folkloric claims of these plants. Besides, safety in the use of folk medicines has been a major public health concern over the year. Therefore, it has become mandatory that relevant authority should take measures in safeguarding the populace on the use of herbal mixtures. Thus, the present review extracted relevant information from different scientific databases and highlighted some problems associated with folk medicines, adverse effects on reproductive systems, issue about safety due to the toxicity of some plants and their toxicity effects with potential therapeutic benefits are discussed.